ผลของวัตถุเจือปนประเภทคาร์โบไฮเดรตต่อสมบัติของเพสต์และเจลสตาร์ชข้าว - ไชยพรรณ ธาราสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Starch is a major component of human food. Apart from its nutritional role, starch also contributes various functional properties to food such as thickening effect and pasting or gelling property. This study aimed to investigate the effects of carbohydrate additives on properties of rice starch (RS) paste and gel. The sugar and sugar alcohal used in this study were fructose, glucose and sorbitol, The prebiotics used in this study were polydextrose, fructo-oligosaccharide (FOS) and inulin. The additives were added at 5, 10, 20 and 30% by weight of starch. Regarding to pasting behavior, addition of sugar and sugar alcohal caused an increase in pasting temperature, with a decrease in peak viscosity, breakdown viscosity and setback viscosity, of rice starch paste (p≤0.05). Sugar and sugar-alcohal addition was found to increase gelatinization temperature and gelatinization enthalpy of rice starch with increasing sugar and sugar-alcohal concentration, glucose and sorbitol posed the most effect on gelatinization temperature and gelatinization enthalpy of rice starch. Sugar and sugar-alcohal addition also posed a retarding effect on rice starch retrogradation, with glucose and sorbitol being more efficient in lowering starch retrogradation as compared to fructose at the same concentration. The content of solid-like fraction was increase while water mobility of the rice starch gel became decreasing with increasing sugar and sugar-alcohal concentration. (p≤0.05). The prebiotics was found that incorporation of prebiotics posed a striking effect on pasting behavior of rice starch. Pasting temperature was found to increase while peak viscosity became decreasing with increasing prebiotic concentration. At the same concentration, the polysaccharide inulin posed a greater effect on pasting temperature than the oligosaccharides, polydextrose and fructo-oligosaccharide, did. With increasing prebiotic concentration, breakdown and setback of the starch paste were found to decrease. In addition, gelatinization temperature exhibited an increasing trend upon adding prebiotics. Prebiotic addition also posed a retarding effect on rice starch retrogradation, with inulin being more efficient in lowering starch retrogradation as compared to polydextrose and fructo-oligosaccharide at the same concentration. The content of solid-like fraction was increase while water mobility of the rice starch gel became decreasing with increasing the prebiotics concentration. (p≤0.05).